2019
DOI: 10.1253/circj.cj-19-0702
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Flow-Gradient Patterns Between Severe Bicuspid Aortic Stenosis and Severe Tricuspid Aortic Stenosis ― Mechanistic Insight From Multimodal Imaging ―

Abstract: Background: We investigated the flow-gradient pattern characteristics and associated factors in severe bicuspid aortic stenosis (AS) compared with severe tricuspid AS. Methods and Results: A total of 252 patients with severe AS (115 bicuspid vs. 137 tricuspid) who underwent aortic valve (AV) replacement were retrospectively analyzed. Patients were classified into 4 groups according to stroke volume index and mean pressure gradient across the AV [normal-flow-high-gradient (NF-HG), low-flow-high-gradient, normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Recently, MDCT has been used as a complement to echocardiography for diagnosing heart valve disease and preoperative evaluation ( 18 , 29 , 30 ). In patients with BAV, MDCT can provide accurate information about the BAV and adjacent structural abnormalities including the aorta, concomitant anomalies, or combined coronary artery disease ( 10 , 11 ). Furthermore, in the era of transcatheter AVR, the use of multimodal imaging is becoming an increasingly essential part of routine clinical practice, particularly for BAV patients with significant AS ( 10 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, MDCT has been used as a complement to echocardiography for diagnosing heart valve disease and preoperative evaluation ( 18 , 29 , 30 ). In patients with BAV, MDCT can provide accurate information about the BAV and adjacent structural abnormalities including the aorta, concomitant anomalies, or combined coronary artery disease ( 10 , 11 ). Furthermore, in the era of transcatheter AVR, the use of multimodal imaging is becoming an increasingly essential part of routine clinical practice, particularly for BAV patients with significant AS ( 10 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BAV often is accompanied by aortopathy, other congenital defects, cardiomyopathies, or infective endocarditis (IE) (7)(8)(9). In the past two decades, echocardiographic surveillance of asymptomatic subjects has increased, and multimodality imaging has been developed and applied in heart valve diseases (10,11). Recently, transcatheter aortic valve replacement (AVR) has been expanded to young age and low risk groups, and treatment methods in BAV patients have diversified (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Standard measurements were performed according to current guidelines (12). Bicuspid AV was diagnosed when only two cusps were unequivocally identified in systole and diastole in the short-axis view, as previously described (8,9,13). In all patients, bicuspid AV was confirmed on cardiac CT and echocardiography.…”
Section: Transthoracic Echocardiographymentioning
confidence: 99%
“…In particular, the discrepancy between EOA Echo and GOA CT is greater in patients with bicuspid AS compared with those with tricuspid AS (3,8). Previous studies have shown different flow gradient patterns, greater jet eccentricity, and less pressure recovery in patients with bicuspid AS (3,8). However, data to determine the utility of GOA CT on assessment for AS severity are scarce, and there are no studies focusing on bicuspid AS.…”
Section: Introductionmentioning
confidence: 99%
“…Differing classifications of BAV have been advocated in the literature, which means that comparisons and nomenclature are not standardized ( 14 , 15 , 16 , 17 ). Importantly, there is no consensus as to associations between the sub-type of BAV and the pattern of valve dysfunction or aortic dilatation ( 14 , 15 , 16 ).…”
Section: Anatomymentioning
confidence: 99%